1997
DOI: 10.1152/jappl.1997.82.2.460
|View full text |Cite
|
Sign up to set email alerts
|

Time- and order-dependent changes in functional and NO-mediated dilation during exercise training

Abstract: Arterial vessel responses to sodium nitroprusside (SNP) and acetylcholine (ACh) were measured in the spinotrapezius muscle of sedentary (Sed) and treadmill-trained (Tr) rats to determine whether these endothelium-dependent (ACh) and -independent (SNP) mechanisms contribute to the training-induced increase in functional vasodilation previously observed. Control and maximal vessel diameters were similar between Sed and Tr. After 8 wk of training, functional dilation (2-, 4-, and 8-Hz contractions) was enhanced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 32 publications
3
47
0
2
Order By: Relevance
“…Thus EX-induced improvements in EDD are distributed heterogeneously throughout skeletal muscle arteriolar networks, and the pattern of distribution of these effects depends on types of training and signal for EDD (i.e., ACh vs. insulin) (95,102). These observations add importantly to the growing body of evidence that highlight differences among vasomotor properties of arteries of different tissues (89), within tissue (8,41,79,89,135,136,151), and along the length of the arterial network (39,46,58,73,77,78,81,83). The relative importance of vascular control mechanisms also differs among muscles (1, 2), and endothelial phenotype varies among and within vascular beds (4,5,7,49,50,81,83,85,87,97,111,112,122).…”
Section: Effects Of Ex On Microvascular Insulin Signaling In T2dmentioning
confidence: 88%
See 1 more Smart Citation
“…Thus EX-induced improvements in EDD are distributed heterogeneously throughout skeletal muscle arteriolar networks, and the pattern of distribution of these effects depends on types of training and signal for EDD (i.e., ACh vs. insulin) (95,102). These observations add importantly to the growing body of evidence that highlight differences among vasomotor properties of arteries of different tissues (89), within tissue (8,41,79,89,135,136,151), and along the length of the arterial network (39,46,58,73,77,78,81,83). The relative importance of vascular control mechanisms also differs among muscles (1, 2), and endothelial phenotype varies among and within vascular beds (4,5,7,49,50,81,83,85,87,97,111,112,122).…”
Section: Effects Of Ex On Microvascular Insulin Signaling In T2dmentioning
confidence: 88%
“…Skeletal muscle fiber type composition and muscle fiber recruitment patterns during exercise have a major influence on vascularization, capillary exchange capacity, vascular structure, mechanisms of vasomotor control, and regional distribution of blood flow within and among muscles during exercise (10,16,63,79,87,97). Importantly, EX alters relationships among muscle fiber type, recruitment patterns, and blood flow (11,82,110,139) by modifying vascular structure, endothelium (37,38,40,71,81,85,96,98,107,120,137,142,150), and vascular smooth muscle (VSM) of skeletal muscle arteries/arterioles (77,80,81). Although many EXinduced vascular adaptations are concentrated in the muscle tissue, having the greatest relative increase in activity during training sessions (11,15,22,55,56,82,84,92,131,138,139), the relative amount of adaptation is not distributed uniformly for any of these parameters (84), and these adaptations are not the same for different types of EX (11,81,82,109,…”
Section: Ex and Skeletal Muscle Microvascular Adaptations In T2dmentioning
confidence: 99%
“…In rat spinotrapezius muscle, as in many other vascular beds, endothelium-derived NO not only exerts a continuous influence on resting arteriolar tone, but also plays an important role in the active moment-to-moment regulation of blood flow [6, 28, 29, 30]. We have reported that this microvascular NO activity is lost after 2 or more weeks of high dietary salt intake [5, 6].…”
Section: Discussionmentioning
confidence: 99%
“…6 and 7, respectively). In the present study, endothelium-dependent vasodilation was assessed by ACh exposure, which is consistently utilized to investigate endothelial function in many vessel types (i.e., conduit through terminal arterioles) in vivo (50). Furthermore, alterations in ACh and endothelium-dependent vasodilation are strongly related to functional changes in perfusion distribution (31).…”
Section: Mechanisms Of Training Induced Vascular Changes In Nonactivementioning
confidence: 94%